Grammatical Problem in the Result Section of Master Theses - Vanda Kristanti; Wisma Yunita; Ira Maisarah (Linguistic, English Education and Art (LEEA) Journal, 2023)
The aim of this research was to investigate the grammatical problems in the result section of master theses and to know the possible causes of grammatical problems in the theses written by the English education postgraduate program students of the Faculty of Teacher Training and Education of the University of Bengkulu. This study used a mixed method. Documentation, a checklist and an interview were the instruments utilized in this mixed-method research. Most of the grammatical problems were investigated quantitatively, and the causes of grammatical problems were studied qualitatively. The corpus of this study was 20 master theses written by English education postgraduate program students who have graduated in 2021. The findings showed that the most frequent grammatical problems found in the result section of the master thesis were incorrect verbs with 39,8% or 51 times, which were dominated by subject-verb agreement and tense confusion which confuse the reader. The cause of the grammatical problems found in the result section of the thesis was carelessness with 39,16% or 94 times. The conclusion of this study provides information about the most frequent grammatical problems and possible causes in the master thesis result section to increase the writer's awareness about the importance of grammatical writing in the result section. Keywords: Grammatical Problems, Result Section, Theses